An update on genetic variants of the NKX2-5 - Kolomenski, Jorge Emilio (2020)
NKX2-5 is a homeodomain transcription factor that plays a crucial role in heart development. It is the first gene where a single genetic variant (GV) was found to be associated with congenital heart diseases in humans. In this study, we carried out a comprehensive survey of NKX2-5 GVs to build a unified, curated, and updated compilation of all available GVs. We retrieved a total of 1,380 unique GVs. From these, 970 had information on their frequency in the general population and 143 have been linked to pathogenic phenotypes in humans. In vitro effect was ascertained for 38 GVs. The homeodomain had the biggest cluster of pathogenic variants in the protein: 49 GVs in 60 residues, 23 in its third α-helix, where 11 missense variants may affect protein–DNA interaction or the hydrophobic core. We also pinpointed the likely location of pathogenic GVs in four linear motifs. These analyses allowed us to assign a putative explanation for the effect of 90 GVs. This study pointed to reliable pathogenicity for GVs in helix 3 of the homeodomain and may broaden the scope of functional and structural studies that can be done to better understand the effect of GVs in NKX2-5 function.